Science as a bridge. Science in action - Kobylarek, Aleksander (Journal of Education Culture and Society, 2018)
The article deals with the concept of science in action. This is a method of conducting science in the interests of the local community and in collaboration with local institutions. Academic research is coupled with practice, with the common aim of solving specific social problems. Knowledge gained in this way enriches global achievements, and at the same time meets the needs of the community. The defining conditions of this process are respect and mutual acknowledgement among co-workers, partnership communication, co-operation focussed on effectiveness and the coupling of theory with practical research, as well as a full-scale diagnosis of the real problems in the institute.